80 jaar wonen in het Stedelijk. - Bergvelt, Ellinoor; Bertheux, Wil; Crommelin, Liesbeth; Eijkhout, Eveline; Thomas, Mienke Simon; Timmer, Petra; de Wilde, Edy (Amsterdam : Stedelijk Museum Amsterdam, 1981)
Aalto, Alvar ; Berkovich, Elmar ; Eschauzier, Frits ; Jacobsen, Arne ; Jansma, Arie ; Kramer, Friso ; Larsen, Jack Lenor ; Liang, Kho ; Mathsson, Bruno ; Polak, Hans ; Rietveld, Gerrit ; Rietveld, Wim ; Salomonson, Hein ; Sandberg, Willem ; Visser, Martin
Lijst van tentoonstellingen 1895-1981 p. 46-48
80 jaar wonen in het Stedelijk, Stedelijk Museum Amsterdam, 2.10 22.11.1981
Nederlands
boek